Pemanfaatan Internet Sebagai Media Penyedia Informasi Perikanan oleh Pembenih Ikan di Balai Benih Ikan Desa Sipungguk Kecamatan Salo Kabupaten Kampar Provinsi Riau - Titra Hidayah; Ridar Hendri; Zulkarnain (JURNAL SOSIAL EKONOMI PESISIR, 2022)
This research was conducted from March to April 2020 at Balai Benih Ikan Sipungguk Village, Kampar regency’ Riau Province. The method used was survey method by making direct observations in the field the collecting data through interviews with a questionnaire. In this study the respondents were 10 fish breeders who used the internet taken by purposive sampling. The result of the study indicate that the fish breeders at the Balai Benih Ikan Sipungguk village, Kampar regency, Riau province, had a productive age of 24-52 years. Fish hatchery education at the undergraduate level was classified as high. The income from a salary of IDR 1.500.000/month was in the medium category, moderate internet usage pathern was 4 hours apart from holidays, the average frequency was 5 hours/day of smartphone usage everyday. The variety of media access consisted of Youtube, Whatsapp, Instagram and Blog. The breedders used the internet to facilitate communication among other breeders, send electronic mail such as Email and Whatsapp, open discussion forums to convey and share information and to find out about developing problems by always updating the latest information on the internet. In general for those related to work in the work group.